Pendampingan Penyusunan Laporan Keuangan Pada Cahaya Cellular - Adhivinna, Vidya Vitta; M Sulkhanul Umam; Putri, Anandita Zulia; Wahyuni, Sri (LPPM IST AKPRIND Yogyakarta, 2023)
ABSTRACT The financial statements record all business activities carried out and then turn them into the final product which contains a summary of business transactions which is used as a periodic performance evaluation. Lack of understanding related to the preparation of financial statements is often a limitation for business actors. So that businesses have difficulty being able to evaluate their performance periodically. Therefore, assistance and training are needed related to recording business activities carried out for business units that have limitations in recording business processes. In order to make it easier for actors to record, it requires the use of computing technology. Selection of the use of existing computing technology must be based on convenience for users so that the goals of implementing technology are achieved. The use of computing technology is based on the convenience of recording business activities including recording sales, purchases and inventories. Recording carried out using the help of computational technology can also improve existing controls because all records carried out are matched with actual conditions in the field. So that if there is a difference between the recording and the real condition, it will be immediately detected. Keywords: register, computation technology, financial statements, sme